REVITALISASI DAN INOVASI WAYANG LANGKA MELALUI PERANCANGAN MODEL PERTUNJUKAN WAYANG GEDOG GARAP RINGKAS - S., Sunardi; Bambang Suwarno; Bagong Pujiono (Institut Seni Indonesia Surakarta, 2015)
This writing is meant to explore and identify wayang gedog; to design a model of wayang gedogshort performance; to compose and publish a guidebook for a practice of wayang gedogperformance; to socialize the short performance of wayang gedog for social appreciation; and tomake a learning media of wayang gedog in VCD. The research targets include identification ofwayang gedog life and derivation; composition of a model design for wayang gedog shortperformance; composition and publication of a guidebook of wayang gedog performancepractice; socialization of a model of wayang gedog short performance to society; composition ofa learning media of wayang gedog in VCD; and publication of this article in an accredited journal.This research applies descriptive qualitatif method and act analysis. The ways executed includelibrary study; observation and documentation; interview; descriptive qualitative analysis;designing a model; trying out the model ; evaluation and model improvement; learning mediapacking; and socializing the model of wayang gedog short performance to the society.Theanalysis shows that revitalization and innovation on the short wayang gedog can be divided intothree variant including: lakon Jaka Bluwo with a palace aesthetic model; lakon Angreni with aâ€œnewâ€ aesthetic model (academic); and lakon Sekar Tanjung with a ruralaesthetic.Keywords: revitalization, innovation, scarce wayang, wayang gedog performance, society.